Early Versus Delayed Dressing Removal in Clean-Contaminated and Contaminated Midline Laparotomy Wounds - Alam, Roshina; Jaleel, Farhat; Siamwala, Tasneem Shabbir; Maria, .; Akram, Qurat-Ul-Ain; Rajput, Akram (Biological and Clinical Sciences Research Journal, 2025)
Surgical site infections (SSIs) remain a major postoperative complication associated with increased morbidity, prolonged hospital stay, and additional healthcare costs. Optimal timing for removal of surgical dressings after midline laparotomy remains debated, particularly in clean and clean-contaminated wounds. Objective: The purpose of this research was to assess whether patients who receive their dressings removed earlier develop fewer superficial SSIs after undergoing midline laparotomy surgery. Methods: After obtaining ethical approval from the institutional review board, this randomised controlled trial was conducted at the Department of General Surgery, Dr. Ruth K.M. PFAU Civil Hospital, Karachi, from 1 July 2024 to 30 December 2024. Through non-probability consecutive sampling, 94 patients aged 18 to 60 years, both genders, admitted for either elective or emergency surgeries, who underwent midline laparotomy procedures with wounds either clean or clean-contaminated wounds were included in the present study. Results: A significant difference was observed in the incidence of superficial surgical site infection (SSI) between the two groups. 64% of patients in the early dressing removal group developed SSIs compared to 85% in the late removal group, indicating a statistically significant reduction in SSIs with early dressing removal (p = 0.02). This finding supports the hypothesis that early dressing removal may contribute to improved postoperative wound outcomes. Conclusion: Early removal of dressing after midline laparotomy within 48 hours has a lower incidence of superficial surgical site infections than delayed removal.